STRATEGI PENGEMBANGAN KOMPETENSI PELAKU USAHA UMKM MENUJU KEBERLANJUTAN USAHA - Makom, Maharani Rona; Adhiani, Budhi; Sumanto, Sumanto; Mardinawati, Mardinawati; Santosa, Teguh Budi (Politeknik Negeri Semarang, 2024)
This study aims to analyse business profile factors through human resource profiles, ICT skills, external environmental support and financial literacy skills that affect business sustainability. The research was conducted using a qualitative research design. The data collection method used interview techniques with five informants from MSME actors in Manding Village, Temanggung, Central Java and triangulated sources to analyse the validity of the data. The results of this study show a description of the condition of business management in Manding Village, Temanggung seen from the profile of SME resources, competence in using ICT, external support and financial literacy. From the interview results, it can be seen that there is still a lack of training intensity, business socialisation assistance, especially related to marketing, technology use and business financial management. Employees only focus on the production process and product manufacturing. There is still a lack of competence in the use of ICT and business financial management. Currently, MSME players in Manding Village, Temanggung still rely on their own capital because there is no capital assistance, incentives or business management facilities from related agencies. The implications of this research are expected to be a consideration for the government to improve the competence of MSME entrepreneurs through training and financing.